A Study of Impact of Early Diagnosis in the Management of Choledochal Cysts of Infancy and Childhood a Experience and Analysis of 205 Cases (Global Journal of Medical Research, 2015)
Introduction: Choledochal cyst not an uncommon encountered pediatric surgical practices. Advances in technology have impacted timing of diagnosis. Advances in instrumentation and surgical access have added yet another way of excion. But the exact impact of early diagnosis on surgery of choledochal cysts have not been analysed and reported. Hence this attempt to analyse the three periods of choledochal cyst, namely 1. PTC (Percutaneous Trans-hepatic Cholangiography) and ERCP (Endoscopic Retrograde Cholangio #x2013; pancreatography), 2. USG (Ultrasonography) and CT Scan (Computerised Tomography era, and 3 .Period of MRCP (Magnetic Resonnace Cholangio #x2013;Pancreaticography) with reagrds to impact of early diagnosis in the management of Choledochal cysts. Materials and Methods: A total of 205 cases of choledochal cysts treated by the team were analysed. The data retrieval was from aaself developed Microsoft Access based soft ware used by senior pediatric surgeon.
Keywords: choledochal cyst; roux en y hepaticodochojejunostomy; anomalous pancreatico biliary portal junction; long channel